(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to analyze the effect of Work-life balance and Reward System on Turnover Intention and analyze the mediating role of Employee Engagement. This research is quantitative. The type of data used is primary data obtained through the distribution of questionnaires. The respondents of this study were millennial and Gen Z employees who worked for digital startup companies in Malang totaling 125 people. The data was analyzed using descriptive analysis and PLS analysis with the help of the SmartPLS version 4 application. The results of the analysis showed that the effect of WLB, reward system, and employee engagement on turnover intention is significantly negative; and then the effect of WLB, reward system on employee engagement is significantly positive. Variable WLB and Variable reward systems have a positive and significant effect on turnover intention through employee engagement. The assumption that there is a relationship between the four variables in theoretical construction, illustrates a relationship that can explain and describe the practical application and implications for the novelty of human resource management theory in the digital and creative industries. The contribution of these findings may help management implement policies and programs that support a balanced work-life balance to improve employee well-being and productivity and decrease turnover intention.